ARGUMENTATIVITY IN THE CONTINUUM OF IMPOLITENESS: A TEXTUAL APPROACH - Oliveira Fernandes, Jessica; Lima de Oliveira, Rafael (Revista de Letras, 2025)
In this paper, based on a brazilian strand of text linguistics (Cavalcante et al., 2022), we assume that argumentativity is a condition of every text and that argumentative motivations influence all strategies of text organization. Thus, using referential processes, which activate references in networks within texts (Matos, 2018), as an analytical criterion, we aim to demonstrate that the use of impoliteness is an argumentative strategy and manifests in texts to varying degrees, one of which is violence, which occupies one of the extremes of what we call, based on Fernandes (2024), the “continuum of impoliteness”. The demonstration of how impoliteness operates strategically is based on the analysis of comments on newspaper profile posts on the social network Instagram. Referential processes are mobilized to highlight levels of impoliteness that act as more or less aggressive ways of marking the commentators' points of view in the text.